The Prevalence of Colistin Resistant Strains and Antibiotic Resistance Gene Profiles in Funan River, China - Tuo, Hongmei; Yang, Yanxian; Tao, Xi; Liu, Dan; Li, Yunxia; Xie, Xianjun; Li, Ping; Gu, Ju; Kong, Linghan; Xiang, Rong; Lei, Changwei; Wang, Hongning; et al. (Frontiers in Microbiology, 2018)
Anthropogenic activities near urban rivers may have significantly increased the acquisition and dissemination of antibiotic resistance. In this study, we investigated the prevalence of colistin resistant strains in the Funan River in Chengdu, China. A total of 18 mcr-1-positive isolates (17 Escherichia coli and 1 Enterobacter cloacae) and 6 mcr-3-positive isolates (2 Aeromonas veronii and 4 Aeromonas hydrophila) were detected, while mcr-2, mcr-4 and mcr-5 genes were not detected in any isolates. To further explore the overall antibiotic resistance in the Funan River, water samples were assayed for the presence of 15 antibiotic resistance genes (ARGs) and class 1 integrons gene (Intl 1). Nine genes, sul1, sul2, int1, aac(6')-Ib-cr, blaCTX-M, tetM, ermB, qnrS, and aph(3’)-IIIa were found at high frequencies (70%-100%) of the water samples. It is worth noting that mcr-1, blaKPC, blaNDM and vanA genes were also found in water samples, the genes that have been rarely reported in natural river systems. The absolute abundance of selected antibiotic resistance genes (sul1, aac(6')-Ib-cr, ermB, blaCTX-M, mcr-1, and tetM) ranged from 0 to 6.0 (log10 GC/mL) in water samples, as determined by quantitative polymerase chain reaction (qPCR). The sul1, aac(6')-Ib-cr, and ermB genes exhibited the highest absolute abundances, with 5.8, 5.8, and 6.0 log10 GC/mL, respectively. The absolute abundances of six antibiotic resistance genes were highest near a residential sewage outlet. The findings indicated that the discharge of resident sewage might contribute to the dissemination of antibiotic resistant genes in this urban river. The observed high levels of these genes reflect the serious degree of antibiotic resistant pollution in the Funan River, which might present a threat to public health.